D‐dimer in Adolescent Pulmonary Embolism. (10th August 2018) - Sharaf, Nematullah; Sharaf, Victoria B.; Mace, Sharon E.; Nowacki, Amy S.; Stoller, James K.; Carl, John C.
Abstract: Background: D‐dimer is used to aid in diagnosing adult pulmonary embolism (PE). D‐dimer has not been validated in adolescents. Clinicians must balance the risk of overtesting with that of a missed PE. D‐dimer may be useful in this context. This study evaluates D‐dimer in PE‐positive and PE‐negative adolescents. Methods: PE‐positive patients < 22 years were diagnosed with PE by computed tomography (CT) or high‐probability ventilation/perfusion, seen at emergency departments (EDs)/hospitals within a 16‐hospital system across two states, January 1998 through December 2016. Of the 189 PE‐positive patients, 88 (46.5%) had a D‐dimer and were matched 1:1 by age, sex, and race to patients suspected of PE but confirmed negative by CT angiogram. Results: Ages of PE‐positive patients ranged from 13 to 21 years, 64 (73%) were female, and 52 (60%) were Caucasian. Mean D‐dimer was significantly higher (3, 256 ng/mL, 95% confidence interval [CI] = 2, 505–4, 006 ng/mL) in PE‐positive versus PE‐negative patients (1, 244 ng/mL, 95% CI = 493–1, 995 ng/mL; p < 0.001). Mean D‐dimer was higher in patients with massive or submassive PE (8, 742 ng/mL, 95% CI = 5, 994–11, 491 ng/mL), followed by PE in central (4, 795 ng/mL [95% CI = 3, 465–6, 125 ng/mL), lobar (3, 758 ng/mL [95% CI = 1, 841–5, 676), and distal (2, 327 ng/mL [95% CI = 1, 273–3, 381 ng/mL]) arteries. When comparing thresholds of positive D‐dimer (≥500, ≥750, and ≥1, 000 ng/mL), D‐dimer had sensitivities of 90, 82, and 67% and specificities of 16, 53, and 67%, respectively. Negative predictive values were 61, 75, and 71% while positive likelihood ratios were 1.1, 1.8, and 2.2, respectively. Conclusions: This study represents the largest available cohort of adolescent patients examining the diagnostic value of D‐dimer for PE. Our results indicate that depending on the threshold selected, D‐dimer can be a sensitive test for PE in adolescents and that discriminative value is higher for a cutoff of 750 ng/mL than that for 500 ng/mL. Prospective studies investigating the diagnostic value of D‐dimer and a clinical decision rule for PE in pediatrics are needed.